The Effect of Midfulness Meditation in Maintaining Blood Pressure in Elderly People with Hypertension: Systematic Review - Sinurat, Diana Nurhayati; Sahar, Junaiti; Rekawati, Etty; Rachmawati, Utami (Indonesian Journal of Global Health Research, 2024)
Elderly with hypertension is group necessary vulnerability​ handling in giving care nursing in a way comprehensive . The purpose of review from systematic This is explore about influence deep mindfulness meditation maintain pressure blood in the elderly with hypertension . Data obtained from Embase, Pubmed, Proquest and Ebscohost databases start from 2019-2023 . Collected articles in review systematic using the keywords "Older people" AND mindfulness meditation AND "Blood Pressure", and "elderly with Hypertension OR transcendental meditation AND Blood pressure ". Selected articles with screening using the PRISMA flowchart in quote from literature This . Review results show that influence mindfulness meditation on pressure blood in patients hypertension give enhancement quality self, reduction in levels of anxiet, stress, as well beneficial For various condition health, influence function and structure brain with fast.